Roflumilast prevented tissue damage caused by lipopolysaccharide-induced sepsis via anti-inflammatory action - Demet Yalçın Kehribar; Lale Saka Baraz; Seda Kırmızıkan; Emre Soner Tiryaki; Mustafa Nusret Çiçekli; Bahattin Avcı; Caner Günaydın (PLoS ONE, 2026)
Sepsis is a life-threatening condition characterized by a dysregulated immune response leading to multiple organ dysfunction. Despite the use of antibiotics and anti-inflammatory drugs, recovery remains limited. Lipopolysaccharide (LPS), an endotoxin from Gram-negative bacteria, is widely used to mimic sepsis-like conditions in animals. This study investigated the anti-inflammatory and protective effects of Roflumilast at two doses (1.5 and 3 mg/kg) in a single-dose LPS-induced sepsis model. Sepsis was induced in rats by intraperitoneal injection of LPS (30 mg/kg), and Roflumilast was administered for 10 days. Liver and kidney injury were evaluated by serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), blood urea nitrogen (BUN), and creatinine levels. Pro-inflammatory cytokines, including tumor necrosis factor (TNF), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6), were measured using ELISA. Histopathological damage and kidney injury molecule-1 (KIM-1) expression were assessed in major organs. LPS significantly increased biochemical and cytokine markers, causing severe tissue damage. While 1.5 mg/kg Roflumilast showed no protective effects, 3 mg/kg markedly reduced inflammatory and injury markers, improved tissue architecture, and decreased KIM-1 expression. These findings suggest that a higher dose of Roflumilast effectively mitigates LPS-induced systemic inflammation and organ injury, supporting its potential as a therapeutic option for sepsis.